Eksplorasi Penerimaan Multiple Micronutrient Supplement (MMS) pada Ibu Hamil: Studi Kasus di Kabupaten Kulon Progo, Yogyakarta: Exploring the Acceptance of Multiple Micronutrient Supplement (MMS) Among Pregnant Women: A Case Study in Kulon Progo District, Yogyakarta - Kurnia Puspitasari; Kandarina, Bernadette Josephine Istiti; Ratrikaningtyas, Prima Dhewi (Amerta Nutrition, 2026)
Background: Based on the 2023 SKI report, the prevalence of anemia in pregnant women reached 27.7%, with a higher rate of 31.4% among women aged 25-35 years. Anemia in pregnancy is generally managed with Iron and Folic Acid (IFA) supplementation. Still, adherence to IFA consumption remains low due to side effects such as nausea and digestive disorders. As an alternative, the Multiple Micronutrient Supplement (MMS) was introduced, which can improve anemia in pregnant women and is 13% more effective than IFA in preventing Low Birth Weight. Objectives: To explore the acceptance of MMS among pregnant women in Kulon Progo District. Methods: Qualitative research with an exploratory case study design. Thirteen informants were selected through purposive sampling, including eight pregnant women as main informants and five supporting informants: two midwives, two pharmacists from Community Health Centers, and one representative from the District Health Office. The study was conducted at the Kulon Progo District Health Office and at the Wates and Samigaluh 2 Primary Health Centers. Data were collected through in-depth interviews and analyzed using Atlas.ti. Results: Acceptance of MMS was influenced by knowledge of MMS, consumption experiences (taste, aroma, and side effects), and support from health workers. Some pregnant women stated that they got bored and did not continue consumption. However, consistent involvement of health workers improved acceptance. Conclusions: Acceptance of MMS among pregnant women is influenced by perceptions, product characteristics, and health worker support. Midwives provide education and monitoring, while pharmacists manage MMS stock recording and reporting.